Press freedom and media ownership are factors that influence media performance: comparative analysis of these factors in USA and Nigeria - Bukar, Modu Alh. Bukar; Kaka, Mohammed; Zannah, Mai Dunoma (Technium Social Sciences Journal, 2019)
The paper is to examine the influence of press freedom and media ownership in the performance of the media institutions in the United States of America and Federal Republic of Nigeria. However, in order to set for such discourse there is indispensable need to review some of the normative theories of the media, which will enable us to locate the appropriate principles guiding the operation of the media in each countries under study. The subdivided into: Abstract, Introduction, Normative Theories of the press, press freedom in United States, press freedom in Nigeria (democracy and press freedom, freedom of information act and conclusion). The analysis concludes that, The United States even has provision in their law and constitution forbidding state interference in the area of information content and dissemination. In Nigeria however, the state control society including the mass media. In this regard, whether media are owned by public or private individuals, they are only meant to service the government in power and were forbidden to criticize the government or its functionaries. The paper recommends that, For Nigerian press to be free the country should militate the all laws or factors that against the press freedom and Members of the Nigerian press must adhere to the ethics of the profession, in order to compete with others freers press of the other countries.